New insights into a complex fungal pathogen : the case of Paracoccidioides spp (2016)
ABSTRACT : Paracoccidioidomycosis is a systemic mycosis endemic to Latin America, withParacoccidioides brasiliensisandP. lutziibeing the causal agents of this disorder. Severalissues have been raised in the 100years since its discovery and in this article we discussfeatures of this fascinating fungal pathogen, including its biology, eco-epidemiology andaspects of its pathogenicity. We also consider some of its virulence determinants, the mostrecent advances in the study of its metabolic pathways and the molecular and genetic re-search tools developed for this research. We also review the animal models used to studyhost–fungal interactions and how the host defence mechanisms against this pathogenwork. Copyright © 2015 John Wiley & Sons, Ltd.